Endodermal sinus tumor of ovary with metastasis from breast carcinoma: a case report - Chandni; Bind, Nirbhay Kumar; Meena, Neeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endodermal sinus tumor is malignant germ cell tumor of ovary. Endodermal sinus tumours (EST) also know as yolk sac tumor are rare about 1% of ovarian malignancies and highly malignant tumours occurring primarily in children and young women. Overall survival is poor. In present case patient was breast cancer survivor and completed her treatment for breast cancer 10 years back. Later on she developed rapidly growing bilateral ovarian mass. Tumor markers of epithelial ovarian tumor were raised. Gross examination was suggestive of Krukenberg tumor and on histopathological examination that was suggestive of endodermal sinus tumor, Finally, Immunohistochemistry helped to conclude the diagnosis of metastatic ovarian tumor from breast carcinoma.